2018
DOI: 10.5812/msnj.87325
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Home-Based Training for Family Caregivers on the Incidence of Bedsore in Patients with Stroke in Ali Ebne Abitaleb Hospital, Zahedan, Iran: A Clinical Trial Study

Abstract: Background: Bedsore is a common problem in patients with stroke, causing an increased number of hospitalizations, increased healthcare costs, and mortality of these patients. Typically, due to their numerous problems, these patients are not able to take care of themselves and thus their care providers play an important role in providing care at their home. Objectives: The present study was conducted with the aim of investigating home-based training on the incidence of bedsore in patients with stroke, during ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…For caregivers to have proper answers, written material about the transmitted information must be arranged for, because it favors learning and allows caregivers to review the addressed contents (8) . A study associated having information with having motivation to provide care (31) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For caregivers to have proper answers, written material about the transmitted information must be arranged for, because it favors learning and allows caregivers to review the addressed contents (8) . A study associated having information with having motivation to provide care (31) .…”
Section: Discussionmentioning
confidence: 99%
“…Emotional support was probably the intervention that was most cited in the literature as being a priority for caregivers, given that its absence can hinder adaptation to the new role and contribute to an increased overload, reduced well-being, and worse health in this population. These problems can lead to a decrease in the quality of care provided to dependent older people (24)(25)(30)(31)(32)(33)(34) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded that home-based training of family members is cost effective and is practical in reducing PU incidence. 22 Many parts of the Saudi multi-faceted program were seen representationally throughout the PUPPs that were reviewed. These included the importance of early identification of high PU risk patients, 22 the use of Braden Scale, 14 the inclusion of a Wound Care Nurse, 19 discharge instructions, 23 as well as the importance of Patient/Family Centered Care.…”
Section: Discussionmentioning
confidence: 99%
“…22 Many parts of the Saudi multi-faceted program were seen representationally throughout the PUPPs that were reviewed. These included the importance of early identification of high PU risk patients, 22 the use of Braden Scale, 14 the inclusion of a Wound Care Nurse, 19 discharge instructions, 23 as well as the importance of Patient/Family Centered Care. 19 All this, in addition to the education provided and interventions (repositioning, assessment, nutrition, skin care) implemented.…”
Section: Discussionmentioning
confidence: 99%